REDENOMINASI RUPIAH DALAM PERSPEKTIF EKONOMI MAKRO ISLAM: ANALISIS FUNGSI UANG, KESTABILAN HARGA, DAN DAMPAKNYA TERHADAP PEREKONOMIAN SYARIAH - Salsabila, Dewi Giri Maryam Salwa; Usmia, Fentiz Istiklalia; Agastya, Mochammad Rievaldo; Wigati, Sri (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
Rupiah redenomination has once again become a strategic discourse amidst demands for monetary stability and more efficient economic management. This research aims to analyze how currency denomination simplification is understood in the context of Islamic macroeconomics, particularly regarding the role of money and currency hedging based on a sharia perspective. Using a qualitative approach focused on desk research, this study explores conventional and sharia economic literature to measure how effective redenomination is in addressing the challenges of price fluctuations and transaction complexity. The analysis shows that although redenomination does not change real values, it provides opportunities for improving pricing systems, increasing transparency, and supporting the efficiency of sharia financial institutions. However, social dynamics such as public miscommunication and the possibility of price manipulation remain a major concern. This research indicates that redenomination has the potential to align with the maqashid sharia, with the important note that it must be accompanied by strict socialization and supervision, so as to strengthen justice and economic welfare for all people.